Prototipe Rancangan Pembelajaran Matematika Untuk Siswa Sekolah Dasar - Putri Zudhah Ferryka; Nela Rofisian (Universitas Muhammadiyah Magelang, 2022)
This study aims to explain the procedure for developing prototypes and producing quality prototypes for learning Mathematics in Elementary Schools. The research method used is Research and Development (R&D). The prototype was prepared using Sugiyono's six development steps including: 1) potential and problems, 2) data collection, 3) product design, 4) design validation, 5) design revision, 6) product trials. Data collection techniques used were interviews and questionnaires. The results of the questionnaire which were distributed to 22 students in grade 15 of SD, the researcher obtained data that 60% of students had difficulty understanding fractional material. From these data the researcher was motivated to relate the material containing the concept of fractions to the song. Prototypes are validated by experts and practitioners. The average score of the three validators is 3.5 in the